2019
DOI: 10.1097/md.0000000000015650
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of apatinib in treatment of osteosarcoma after failed standard multimodal therapy

Abstract: Recently, apatinib has been shown to be effective in treating sarcoma. This study aimed to assess the safety and efficacy of apatinib in the treatment of patients with osteosarcoma after failed of standard multimodal therapy and to compare the therapeutic effects of apatinib on osteosarcoma between high-dose group and low-dose group. A total of 27 patients with osteosarcoma who received apatinib between January 2016 and August 2017 were retrospectively reviewed. Among the 27 patients, the objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 41 publications
2
10
1
Order By: Relevance
“…No treatment-related deaths were observed. The PR rate in this trial was significantly higher than that reported by retrospective studies ( 42 , 43 ). It may be due to the high dose of apatinib, which was 750 mg per day in the registered trial, compared with 500 mg per day in retrospective studies.…”
Section: Tkis Reported In Registered Clinicaltrials For Osteosarcoma contrasting
confidence: 78%
“…No treatment-related deaths were observed. The PR rate in this trial was significantly higher than that reported by retrospective studies ( 42 , 43 ). It may be due to the high dose of apatinib, which was 750 mg per day in the registered trial, compared with 500 mg per day in retrospective studies.…”
Section: Tkis Reported In Registered Clinicaltrials For Osteosarcoma contrasting
confidence: 78%
“…As a multitarget TKI marketed for the treatment of advanced or metastatic gastric cancer in China, apatinib has been shown to be effective for the treatment of osteosarcoma. In our previous work, we found that the incidence of pneumothorax in patients with osteosarcoma treated with apatinib was 18.18%-31.58% [10,11]. which was similar to the results of other studies [5,12].…”
Section: Introductionsupporting
confidence: 90%
“…All TKIs with promising preclinical and clinical effectiveness against sarcoma, including apatinib, anlotinib, axitinib, imatinib, pazopanib, regorafenib, sorafenib, and sunitinib, target multiple angiogenic and growth-promoting receptor tyrosine kinases, as shown in Table 7. Apatinib and anlotinib, the only two domestically developed multi-target TKIs, have been marketed and used widely for the treatment of advanced sarcomas in China [17,18,21]. Although many clinical studies of apatinib and anlotinib have begun to recruit patients with sarcoma (http://www.chictr.org.cn), this study is the first to simultaneously investigate the effectiveness and safety of these two drugs in patients with advanced sarcomas.…”
Section: Discussionmentioning
confidence: 99%